Novel Expanding Renal Cell Carcinoma Biomarkers - Francesco Claps, Maria Carmen Mir (Société Internationale d’Urologie Journal)
Identification of reliable molecular biomarkers that can complement clinical practice represents a fascinating challenge in any cancer field. Renal tumors are usually asymptomatic and incidentally identified during imaging studies undertaken for unrelated causes. However, in 25% to 30% of patients the first diagnosis is accompanied by symptoms and associated with distant metastasis. Thus, early diagnosis may reduce the risk of disease progression also avoiding side effects of inadequate treatments. Moreover, the ability to categorize patients' risk of recurrence after radical treatment, or even predict benefit from a target therapy, represents a compelling challenge. Here we review the current state-of-the-art on RCC biomarkers, particularly focusing on the new approaches of genomics, liquid biopsy, proteomics, and metabolomics.